PENGARUH MODEL KOOPERATIF TWO STAY TWO STRAY BERBANTUAN MEDIA WORDWALL TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS IV SEKOLAH DASAR - Faizah Mawaddah; Ahmad Syarif; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Two Stay Two Stray cooperative learning model assisted by Wordwall media on the procedural text writing skills of fourth grade elementary school students. The research was conducted at SDN 19/1 Muara Tembesi. The method used was a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The sample consisted of 19 fourth grade students. Data were collected through writing tests and observation sheets. Data analysis techniques included normality test and hypothesis testing. The results showed that the implementation of the Two Stay Two Stray model assisted by Wordwall media significantly improved students' procedural text writing skills. This improvement was indicated by the increase in posttest scores compared to pretest scores. Thus, the learning model assisted by interactive media is effective in improving students' writing skills